ALIRAN KAS, TINGKAT HUTANG, PERBEDAAN ANTARA AKUNTANSI DAN LABA FISKAL PADA PERSISTENSI LABA : BUKTI DARI PERUSAHAAN OTOMOTIF - Kemal Al Hafiz; Isnan Murdiansyah (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
This study aims to analyze the effect of cash flow, debt levels, book tax differences on profit persistence. The measurement of profit persistence focuses on the regression coefficient of present profit against previous earnings. This research uses data from companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. The number of research samples was 7 companies obtained by purposive sampling method. The source of research data is secondary data. The analysis technique used in this study is multiple linear regression analysis. The results of the analysis show that cash flow (X1) has no effect on profit persistence, debt level (X2) has no effect on book tax differences (X3) has no effect on profit persistence.